Implementasi Sistem Manajemen Kesehatan Dan Keselamatan Kerja (SMK3) Di PT. Mega Andalan Kalasan Yogyakarta - Erna Desi Faradinah; Azarine Dwinta Framudella; Dessi Setiyaningrum (Multidisciplinary Journal, 2022)
The Occupational Health and Safety Management System (SMK3) is an important part of the protection of the workforce so that workers remain safe, healthy, and safe. The implementation of SMK3 in the company will avoid the risk of moral and material losses, loss of working hours, and safety caused by accidents. In every year, PT Mega Andalan Kalasan has a work accident that results in losses for the company and must be taken to the hospital. Accidents that occur such as broken fingers, pinched fingers, eyes affected by grinding fire and so on. This study aims to determine the implementation of the Occupational Health and Safety Management System (SMK3) at PT. Mega Andalan Kalasan Yogyakarta. This type of research is qualitative by means of observation, this method is more inclined to descriptive results. The sampling technique was carried out by in-depth interviews, exposure from sources and purposive sampling of employees. PT. MAK Yogyakarta has tried the risk of work accidents, physical factors, chemical factors, biological factors, physiological factors (ergonomics), psychological factors and risk control measures, namely training (internal and external), appropriate work tools, installation of signs, provision of fire extinguishers, inspection Health (initial and routine), Environmental inspection or measurement, Provision of first aid kits, Provision of PPE, Simulation and Insurance. Implementation of Occupational Health and Safety Management System (SMK3) at PT. Mega Andalan Kalasan (MAK) Yogyakarta is quite good in terms of the risk of work accidents, risks and hazards of work accidents and the legal basis used in its application is in accordance with ISO 9001 and OHSAS 18001 and PP No. 50 of 2012.